Peningkatan Pengetahuan dan Keterampilan Ibu Rumah Tangga dalam Pengolahan Tanaman Obat Keluarga (TOGA) sebagai Ramuan Obat Tradisional - Nurul Qamariah; Rezqi Handayani; Susi Novaryatiin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
This community service activity aims to increase the knowledge of homemakers about the efficacy of the family medicinal plants (TOGA) scientifically, improve the knowledge and skills of homemakers to process TOGA as an option in treatment therapy. Held at Langgar Nurul Iman as a place for routine activities for homemakers on Jalan Sulawesi Gang Pelita No.41 RT.004/RW.002 Langkai Village, Pahandut Subdistrict, Palangka Raya City, Central Kalimantan. Through this activity, the knowledge and skills of homemakers in processing traditional herbs as an effort to promote, preventive and curative can be improved.